Ornithodoros tick vector competence characterization for African swine fever virus and study of two vector competence determinants : virus strain – vector relationship and tick saliva influence on domestic pig infection - (:unkn) unknown (My University, 2015)
African swine fever (ASF) is a contagious hemorrhagic disease with disastrous financial consequences for pig industry, as no vaccine or treatment exists. This infection is caused by a DNA virus, only member of the Asfarviridae family that can be directly transmitted between swine or by a non-compulsory vector, the Ornithodoros tick. Ornithodoros ticks play a role in the persistence of the disease within wild and domestic suids in Africa. They were also involved in resurgences of outbreaks in some pig farms in the Iberian Peninsula in 1970-1980. ASF, eradicated in Europe at the end of the 1980’s except in Sardinia, was reintroduced in Georgia in 2007 then spread towards the Eastern European Union. The question of the tick vector competence for ASF virus (ASFV) and its related determinants is of importance in the risk assessment of endemisation/spread of the disease in Europe or elsewhere.The first chapter of this thesis aims to characterize Ornithodoros tick vector competence for ASFV and to highlight a common pattern to qualify it. For this purpose, a systematic review of the studies carried out on the vector competence of one or more tick species for one or more ASFV, was performed on the last 50 years publications. A high variability of the results obtained for different couples “tick-virus” was highlighted. As most of the papers describe partial evaluation of the vector competence and because of the high number of methods used to perform these assessments, it was definitively very difficult to compare these results, and to propose common patterns. However, each of these studies revealed a part of the mechanisms that participated to the adaptation in the couple “tick-virus”, and suggested the importance of different determinants, out of them, two were experimentally assessed as described in the two other chapters.The second chapter of this thesis describes the adaptation “tick-virus” through the experimental infection of three different
Keywords: African Research